Estimation of piezoelectric material parameters of ring-shaped specimens - Friesen, Olga; Claes, Leander; Feldmann, Nadine; Henning, Bernd (tm - Technisches Messen)
The estimation of accurate piezoelectric material parameters is a fundamental prerequisite for simulation-driven design of piezoelectric actuators and sensors. Previous studies show that a full set of material parameters can be determined in an inverse procedure using a single disc-shaped specimen with an electrode structured for increased sensitivity with respect to all material parameters. However, in the case of high-power actuator applications, ring-shaped piezoelectric components are often employed, necessitating an adaptation of the previously developed method. The alteration in geometry introduces some advantages. Accordingly, there is no longer any requirement to modify the electrode structure in order to enhance sensitivity. The method to estimate the material parameters presented here consists of a total of three stages. An initial, approximate estimation of the material parameters is determined using analytical approximations for the resonance frequencies from the IEEE standard. These values are optimised in an inverse procedure that employs analytic expressions for the electrical impedance of piezoelectric rings as the forward model. Further refinement is achieved by using Finite Element (FE) simulations as the forward model again in an inverse procedure. The method is applied to electrical impedance measurement data, yielding material parameters for hard piezoelectric rings. The result shows a good agreement between the simulation and measurement results, indicating realistic material parameter values.

Neuronale Netze zur Startwertschätzung bei der Identifikation piezoelektrischer Materialparameter - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars (tm - Technisches Messen)

L∞ blow-up in the Jordan-Moore-Gibson-Thompson equation - Nikolić, Vanja; Winkler, Michael (Nonlinear Analysis)

Diminishing Domain Mismatch for DNN-Based Acoustic Distance Estimation via Stochastic Room Reverberation Models - Gburrek, Tobias; Meise, Adrian Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (2024 18th International Workshop on Acoustic Signal Enhancement (IWAENC))

Robust Funnel Model Predictive Control for Output Tracking with Prescribed Performance - Berger, Thomas; Dennstädt, Dario; Lanza, L.; Worthmann, K. (SIAM Journal on Control and Optimization)

Funnel MPC for nonlinear systems with arbitrary relative degree - Berger, Thomas; Dennstädt, Dario (Automatica)

Model predictive control of a magnetic levitation system with prescribed output tracking performance - Oppeneiger, Benedikt; Lanza, Lukas; Schell, Maximilian; Dennstädt, Dario; Schaller, Manuel; Zamzow, Bert; Berger, Thomas; Worthmann, Karl (Control Engineering Practice)

Sampled-data funnel control and its use for safe continual learning - Lanza, Lukas; Dennstädt, Dario; Worthmann, Karl; Schmitz, Philipp; Şen, Gökçen Devlet; Trenn, Stephan; Schaller, Manuel (Systems & Control Letters)

On Model Predictive Control with Sampled-Data Input for Output Tracking with Prescribed Performance - Dennstädt, Dario; Lanza, Lukas; Worthmann, Karl (2024 European Control Conference (ECC))

Evaluating Supply Scenarios for Hydrogen and Green Fuels from Canada, Chile, and Algeria to Germany via a Techno-Economic Assessment - Seeger, Karl; Genovese, Matteo; Schlüter, Alexander; Kockel, Christina; Corigliano, Orlando; Díaz Canales, Edith Benjamina; Fragiacomo, Petronilla; Praktiknjo, Aaron (United States Association for Energy Economics (USAEE) & International Association for Energy Economics (IAEE) Research Paper Series)

Dual-Active Bridge Sequential Pareto Optimization for Fast Pre-Design and Final Component Selection - Förster, Nikolas; Wallscheid, Oliver; Schafmeister, Frank (2024 IEEE Design Methodologies Conference (DMC))
Keywords: MOSFET; Thermal resistance; Surface resistance; Bridge circuits; Zero voltage switching; Pareto optimization; Capacitance; Numerical simulation; Optimization; Resistance heating; Pareto Optimization; Dual-Active Bridge; ZVS; Inductor Optimization; Transformer Optimization; Heat Sink Optimization

Implementing Strategic Environmental Assessment (SEA) in the Global South, a challenge: Nicaragua as a case study. - Díaz Canales, Edith Benjamina; Avila , Alfredo; Schlüter, Sabine; Lacayo, Erick; Schlüter, Alexander (19th Conference on Sustainable Development of Energy, Water and Environment Systems)

Vorwort - Herzig, Bardo; Eickelmann, Birgit; Schwabl, Franziska; Schulze, Johanna; Niemann, Jan (Lehrkräftebildung in der digitalen Welt Zukunftsorientierte Forschungs- und Praxisperspektiven)

Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven

Anthropological Dimension of Wartime Ecocide: Ecofeminist Methodological Assessments - Karpenko, Kateryna I.; Hagengruber, Ruth Edith; Nielsen, Cynthia R. (Anthropological Measurements of Philosophical Research)
The authors aim to disclose the anthropological dimension of ecocide during and after Russia’s war against Ukraine, relying on the multidisciplinary practices and intellectual production of ecofeminist women thinkers, including philosophers, sociologists, historians, psychologists, and others. The theoretical basis methodological approaches in philosophical anthropology, phenomenology, analytical philosophy, communicative philosophy, existentialism, ethics of justice, and ethics of care determine the study’s theoretical basis. Originality. For the first time, a systematic analysis of the anthropological dimension of ecocide has been carried out based on ecofeminist methodology. The specifics of the Ukrainian resistance to ecocide were revealed as part of a single struggle – an anti-imperial and ecological struggle for independence and prosperity. It is emphasized that during the war, the opposition to ecocide is a component of the fight for national sovereignty and territorial integrity of the country, and therefore, the ideas of pacifism in this period are subordinated to this primary goal. After the war, preventing threats of ecocide should become an integral part of the struggle for stable peace and prosperity. Ecofeminist pacifist perspectives should be a priority among the most essential goals for that period. Conclusions. Ecofeminist methodological assessments offer valuable insights into the anthropological dimension of ecocide in wartime and post-war contexts, highlighting the complex interplay between gender, violence, and environmental destruction. By focusing on the experiences and perspectives of women and marginalized communities, ecofeminist analyses contribute to a more holistic understanding of ecocide and its impacts on both human populations and ecosystems.

Teaching Women Philosophers—Ideas and Concepts from Women Philosophers’ Writings Over 2000 Years - Hagengruber, Ruth Edith (Teaching Women Philosophers. Women in the History of Philosophy and Sciences.)
Why should the philosophy of the Pythagoreans be reduced to Pythagoras alone? Why do we learn about the ego only from Husserl and not from Conrad-Martius? What do we know about free will from Helene Druskowitz and why is Émilie Du Châtelet unknown to us? Many of the philosophers in this collection were celebrities in their own time. What can we gain from rediscovering the knowledge of women philosophers? Philosophy reflects the foundations on which we organise our world. There is no doubt that women create structures that shape our world. Over the centuries, women thinkers have formulated ideas and concepts to explain our world and to call for its reorganisation. This collection offers a selection of these ideas and concepts from over 2000 years. The new history of philosophy emerges in this way. It provides the basis for teaching and future research. Rooted in the past, it can use that experience to contribute to a new and better way forward.

Teaching Women Philosophers

Understanding the Wettability of C1N1 (Sub)Nanopores: Implications for Porous Carbonaceous Electrodes - Lamata‐Bermejo, Irene; Keil, Waldemar; Nolkemper, Karlo; Heske, Julian; Kossmann, Janina; Elgabarty, Hossam; Wortmann, Martin; Chorążewski, Mirosław; Schmidt, Claudia; Kühne, Thomas D.; Lopez Salas, Nieves; Odziomek, Mateusz (Angewandte Chemie International Edition)
Abstract Understanding how water interacts with nanopores of carbonaceous electrodes is crucial for energy storage and conversion applications. A high surface area of carbonaceous materials does not necessarily need to translate to a high electrolyte‐solid interface area. Herein, we study the interaction of water with nanoporous C 1 N 1 materials to explain their very low specific capacitance in aqueous electrolytes despite their high surface area. Water was used to probe chemical environments, provided by pores of different sizes, in 1 H MAS NMR experiments. We observe that regardless of their high hydrophilicity, only a negligible portion of water can enter the nanopores of C 1 N 1 , in contrast to a reference pure carbon material with a similar pore structure. The common paradigm that water easily enters hydrophilic pores does not apply to C 1 N 1 nanopores below a few nanometers. Calorimetric and sorption experiments demonstrated strong water adsorption on the C 1 N 1 surface, which restricts water mobility across the interface and impedes its penetration into the nanopores.

35 challenges in materials science being tackled by PIs under 35(ish) in 2024 - Lázaro, Isabel Abánades; Anastasaki, Athina; Ardoña, Herdeline Ann M.; Arguilla, Maxx Q.; Bati, Abdulaziz S.R.; Batmunkh, Munkhbayar; Besford, Quinn A.; Browne, Michelle P.; Bryant, Saffron J.; Carlotti, Marco; Contini, Claudia; Delaney, Colm; et al. (Matter)

Template‐Induced Graphitic Nanodomains in Nitrogen‐Doped Carbons Enable High‐Performance Sodium‐Ion Capacitors - Li, Chun; Song, Zihan; Liu, Minliang; Lepre, Enrico; Antonietti, Markus; Zhu, Junwu; Liu, Jian; Fu, Yongsheng; Lopez Salas, Nieves (ENERGY & ENVIRONMENTAL MATERIALS)
Sodium‐ion capacitors (SICs) have great potential in energy storage due to their low cost, the abundance of Na, and the potential to deliver high energy and power simultaneously. This article demonstrates a template‐assisted method to induce graphitic nanodomains and micro‐mesopores into nitrogen‐doped carbons. This study elucidates that these graphitic nanodomains are beneficial for Na + storage. The obtained N‐doped carbon (As8Mg) electrode achieved a reversible capacity of 254 mA h g −1 at 0.1 A g −1 . Moreover, the As8Mg‐based SIC device achieves high combinations of power/energy densities (53 W kg −1 at 224 Wh kg −1 and 10 410 W kg −1 at 51 Wh kg −1 ) with outstanding cycle stability (99.7% retention over 600 cycles at 0.2 A g −1 ). Our findings provide insights into optimizing carbon's microstructure to boost sodium storage in the pseudocapacitive mode.